1997
DOI: 10.1038/sj.onc.1201166
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the transforming growth factor-β type II receptor in human cell lines resistant to growth inhibition by transforming growth factor-β

Abstract: The transforming growth factor-b (TGF-b) binds the type II TGF-b growth factor receptor (RII) to inhibit the growth of most epithelial tissues. Most human colon and gastric cancers with microsatellite instability (MI) have frameshift mutations in polynucleotide repeats within the RII coding region; these mutations truncate the receptor protein and disable the serine/threonine kinase to produce TGF-b resistance. To further investigate the type, frequency and tissue distribution of RII mutations, we selected 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 29 publications
(43 reference statements)
1
24
0
Order By: Relevance
“…A significant number of human carcinomas and cancer cell lines lose sensitivity to negative growth regulation by transforming growth factor b (TGF-b) (Vincent et al, 1997). In biliary tract cancers, it was reported that 16% (five out of 32 primary biliary carcinomas) had point mutations in the DPC4 gene (Hahn et al, 1998).…”
Section: Pcr-sscp Exonmentioning
confidence: 99%
“…A significant number of human carcinomas and cancer cell lines lose sensitivity to negative growth regulation by transforming growth factor b (TGF-b) (Vincent et al, 1997). In biliary tract cancers, it was reported that 16% (five out of 32 primary biliary carcinomas) had point mutations in the DPC4 gene (Hahn et al, 1998).…”
Section: Pcr-sscp Exonmentioning
confidence: 99%
“…Most mutations of the TbR-II gene reported so far are located in exon 3, 5, and 7. 43 As microsatellite regions exist in exon 3 and 7 of the TbR-II gene, 44 somatic mutations in these regions may relate to microsatellite instability or replication error. 45,46 Mutations in exon 5 are sporadic and are not associated with replication error.…”
Section: Tgf-b1mentioning
confidence: 99%
“…Likewise, there were no somatic mutations in a series of 51 human tumor cell lines which included 20 cell lines known to be resistant to TGF-b 1 . Although we recently reported mutations in the TGF-b type II receptor in three colon cell lines with microsatellite instability (Vincent et al, 1997), the mechanisms for TGF-b 1 resistance remain unknown for most human cell lines. Our results are consistent with the ®ndings of Riggins and coworkers (Riggins et al, 1997) who found no mutations in 167 early-passage human cell lines representing tumors of the colon, breast, brain, lung, pancreas, head and neck and others.…”
mentioning
confidence: 99%
“…No homozygous deletions were detected in 40 primary gastric cancers from Chinese patients surgically resected at the School of Oncology, Beijing Medical University and 51 human cancer cell lines that included tumors of the head and neck, retina, breast, lung, esophagus, stomach, liver, colon, pancreas, cervix, skin, ovary, and blood (Table 1) (Gemma et al, 1996;Vincent et al, 1997) by PCR ampli®cation of each exon ( Figure 5). This set of cell lines included 20 that were reported to be completely or substantially resistant to growth inhibition by TGF-b 1 (Table 1) (Fynan and Reiss, 1993;Vincent et al, 1997). We did not ®nd aberrant bands in SSCP analysis of the same PCR products.…”
mentioning
confidence: 99%
See 1 more Smart Citation